2010
DOI: 10.1093/icesjms/fsq071
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of deep-water corals of the Flemish Cap, Flemish Pass, and the Grand Banks of Newfoundland (Northwest Atlantic Ocean): interaction with fishing activities

Abstract: Murillo, F. J., Durán Muñoz, P., Altuna, A., and Serrano, A. 2011. Distribution of deep-water corals of the Flemish Cap, Flemish Pass, and the Grand Banks of Newfoundland (Northwest Atlantic Ocean): interaction with fishing activities. – ICES Journal of Marine Science, 68: 319–332. The distribution of deep-water corals of the Flemish Cap, Flemish Pass, and the Grand Banks of Newfoundland is described based on bycatch from Spanish/EU bottom trawl groundfish surveys between 40 and 1500 m depth. In all, 37 taxa o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Other species found in this study confirm those recorded in extensive fishery and trawl surveys of the Grand Banks and surrounding areas, though several studies did not report Chrysogorgia agassizi (Gass & Willison 2005, Wareham & Edinger 2007, Murillo et al 2010). Our cruise identified at least 3 species of Flabellum, compared to the one (F. alabastrum) recorded by the other survey methods (Wareham & Edinger 2007, Murillo et al 2010. Mortensen et al (2006b) found F. macandrewi along the Scotian Shelf and within The Gully off Nova Scotia, but not off Newfoundland and Labrador.…”
Section: Large Scale Patterns In Species Distributions and Diversitysupporting
confidence: 82%
See 2 more Smart Citations
“…Other species found in this study confirm those recorded in extensive fishery and trawl surveys of the Grand Banks and surrounding areas, though several studies did not report Chrysogorgia agassizi (Gass & Willison 2005, Wareham & Edinger 2007, Murillo et al 2010). Our cruise identified at least 3 species of Flabellum, compared to the one (F. alabastrum) recorded by the other survey methods (Wareham & Edinger 2007, Murillo et al 2010. Mortensen et al (2006b) found F. macandrewi along the Scotian Shelf and within The Gully off Nova Scotia, but not off Newfoundland and Labrador.…”
Section: Large Scale Patterns In Species Distributions and Diversitysupporting
confidence: 82%
“…Murillo et al (2010) found only 17 species on the Grand Banks during their bottom trawl surveys, Mortensen et al (2006b) identified 12 species on the Grand Banks using a variety of techniques, and Wareham & Edinger (2007) recorded 30 species throughout all Newfoundland and Labrador waters. In a towed camera survey of more southerly canyons, found at least 12 species of corals in Baltimore Canyon, 13 species in Lydonia Canyon, and 16 species in Oceanographer Canyon.…”
Section: Large Scale Patterns In Species Distributions and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Benthic fauna samples were sorted on board and preserved (70% ethanol or 4% buffered formaldehyde-seawater solution) for further identification analysis. Even if the bottom-trawl by-catch collected information did not allow for a detailed habitat mapping of VMEs, it provided a valuable indication of VME presence/absence that can be used to propose conservation measures, such as candidate areas for bottom fishery closures [23]. .…”
Section: Methodsmentioning
confidence: 99%
“…Several authors [2,3,[16][17][18][19][20][21][22][23] have studied the potential disturbance of the seabed by bottom otter trawls and the possible negative effects on the structure of benthic communities. In recent years, several resolutions of the United Nations General Assembly [24][25][26][27][28] on sustainable fisheries made a call to States and RFMOs to identify vulnerable marine ecosystems (VMEs) and determine whether bottom fishing activities would cause a significant adverse impact on such ecosystems.…”
Section: Introductionmentioning
confidence: 99%